Quantifying the planarity of the field hockey hit - Willmott, A.; Dapena, J. (2008 Annual Meeting (NACOB) Ann-Arbor, 2008)
The concept of a `swing plane` in golf was popularized by Cochran and Stobbs (1968) based upon their qualitative observation that the clubhead moves in a single inclined plane for much of the downswing. The assumption of planar arm and club motions has been central to most modeling of the swing, though its validity has been questioned (see, for example, Coleman and Anderson, 2007). The planarity of the field hockey hit has not been investigated. The purpose of this study was to initiate such an analysis by developing a quantitative version of Cochran and Stobbs` approach and applying it to the path followed by the stickface during the downswing.